Child sexual abuse in Zimbabwe: prevention strategies for social workers - Muridzo, Noel G.; Malianga, Effie (African Journal of Social Work, 2020)
The phenomenon of child sexual abuse (CSA) remains topical in Zimbabwe. Statistics, literature and debate reflect not only increased scientific interest in child sexual abuse and its potential effects but also growing public concern about this form of child maltreatment. The sexual abuse of children crosses cultural and economic divides. Sexual abuse can lead to long-lasting, even life-long consequences and is a serious problem on individuals, families and societies. Social workers by nature of their work, intervene at the individual, family and societal level. This paper will explore the definition of CSA, its effects and prevention strategies. The paper adopts Meili‘s model of prevention which suggests prevention of CSA at primary, secondary and tertiary levels. The authors conclude that social workers in Zimbabwe have a role to play at all the three levels of intervention.